The impact of logistics on four dimensions of food security in eveloping Countries - Subramaniam, Yogeeswari; Masron, Tajul Ariffin; Mohd Naseem, Niaz Ahmad (Springer Science and Business Media LLC, 2022)
With zero hunger in the heart of the Food Agriculture Organization (FAO), FAO’s end goal is to ensure that all people always have physical and economic access to sufficient and nutritious food. However, the number of hungry people in the world can be considered as relatively high and the path to reach the level called “enough” food or “perfect” food security still has a long way to go. Considering the complicated nature of food security, this study aims to investigate the impact of logistic performance on food security in 51 developing countries covering the period 2010–2016, under 4 unique dimensions of food security. Applying the generalized method of moments (GMM), the results provide supportive evidence that the level of food security tends to be improving in countries with a higher level of logistic performance. Similarly, it is observed that every dimension of food security, namely food availability, accessibility, utilization, and stability, can be improved with better logistics. Therefore, the overall result suggests that policymakers should improve the level of logistic performance, which is generally far below that in developed countries, so that it can form the fundamental ground toward alleviating hunger and improving the food supply.